Day 1 Tue, June 10, 2014 2014
DOI: 10.2118/170057-ms
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behaviour and Viscosity Reduction of CO2-Heavy Oil Systems at High Pressures and Elevated Temperatures

Abstract: Techniques have been developed to experimentally and theoretically determine phase behaviour and viscosity reduction of CO 2 -heavy oil systems at high pressures and elevated temperatures. Experimentally, vapour-liquid phase boundaries (i.e., saturation pressure lines) and the swelling factors are measured by conducting PVT tests at pressures up to 11094.0 kPa and temperatures up to 362.75 K, respectively. The viscosity of CO 2 -saturated heavy oil is measured at 319.15 K. Theoretically, the heavy oil sample i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The following modified alpha function employed in the PR EOS has been found to more accurately describe the phase behavior of both pure substances and alkane solvent(s)–CO 2 –heavy oil systems by treating heavy oil as one pseudocomponent and multiple pseudocomponents. In this study, the PR EOS together with the modified alpha function has been employed to determine the moles of the evolved gas under thermodynamic conditions, n em , for the alkane solvents–CO 2 –heavy oil systems.…”
Section: Mathematical Formulationsmentioning
confidence: 99%
“…The following modified alpha function employed in the PR EOS has been found to more accurately describe the phase behavior of both pure substances and alkane solvent(s)–CO 2 –heavy oil systems by treating heavy oil as one pseudocomponent and multiple pseudocomponents. In this study, the PR EOS together with the modified alpha function has been employed to determine the moles of the evolved gas under thermodynamic conditions, n em , for the alkane solvents–CO 2 –heavy oil systems.…”
Section: Mathematical Formulationsmentioning
confidence: 99%
“…Supercritical CO 2 has great potential as a fracturing fluid to stimulate this special reservoir, which can cause wettability alteration on the low permeability reservoir and lower the surface tension and viscosity of the oil to improve the displacement [9][10][11][12]. The studies by Zhang et al [13] indicate that SC-CO 2 is considered as an ideal nonaqueous fracturing fluid which can produce a denser crack network.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few attempts have been made to determine the phase behavior of solvent/CO 2 /heavy oil mixtures with the existence of water/steam at high pressures and elevated temperatures. This is due to the following reasons: (1) it is technically difficult to perform three-phase ALV PVT tests at high pressures and elevated temperatures; (2) emulsion phenomenon makes it challenging to clearly observe the interface between water and heavy oil; and (3) temperature limitation of the current PVT equipment makes it impossible to conduct experiments at high temperatures. , Also, no studies have been found on the investigation of multiphase boundaries for solvent/CO 2 /water/heavy oil systems in the H – T diagrams, which is crucial for the field design of steam-solvent coinjection processes for heavy oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%